Block-based fuzzy-image authentication method. Issue 5 (3rd September 2019) - Tuncer, Türker
Abstract: Fragile watermarking methods have been widely used for image authentication. A novel image-authentication method based on fuzzy coding is presented in this work. This method is a block-based method and it consists of watermark generation, watermark embedding, watermark extraction, tamper detection, and image recovery phases. First, the cover image is divided into nonoverlapping blocks. In the watermark-generation step, fuzzy sets and fuzzy coding are used. To generate fuzzy sets, three threshold points are selected from a histogram of the cover image and fuzzy sets are created by using these threshold points. Memberships of pixels are calculated to generate features. Fuzzy coding is used to generate the watermark. The watermark-embedding function uses ±1 data hiding function for each block. Therefore, high visual quality is achieved. The generated watermark is compared with the extracted watermark in the tamper-detection phase. Finally, a new image-recovery algorithm is proposed for recovering tampered areas. To evaluate the proposed method, visual quality, tamper detection ability, image recovery capability, and computational complexity were used. The experimental results clearly indicated that the proposed method was a success.